The building of the Ministry of Foreign Affairs - Pavlović Marina S.; Mihajlov Saša J. (Nasleđe, 2022)
One of the most monumental buildings of Interwar Academicism in Serbia, the building of the Ministry of Foreign Affairs at Kneza Miloša 24-26, forms, together with the Government Building - the former Ministry of Finance - a harmonious ensemble shaped by the architect Nikolay Petrovich Krasnov. Although it was not built for the needs of the Ministry of Foreign Affairs, but rather for two other ministries (the Ministry of Forestry and Mining and the Ministry of Agriculture and Waterworks), the monumentality of the building corresponds to the importance of the institution that it plays host to. Ever since the formation of Serbian statehood at the beginning of the 19th century, there was a close and interweaving connection between the royal court and the institution in charge of foreign policy, which affected the choice, representativeness, location, and also the stylistic expression of the building in which the Ministry of Foreign Affairs was situated. The paper aims to comprehensively investigate the process of design and construction of the building of the Ministry of Foreign Affairs, and to further contextualize aspects of its construction. With a further aim being to comprehensively research the correlation of the siting and aesthetic projection of the headquarters of the Ministry of Foreign Affairs from the first office of the 'Foreign Department' of Miloš Obrenović to the current building in Kneza Miloša, special attention is also paid to the history of the actual location of the Ministry of Foreign Affairs, i.e. also its previous headquarters.